2016
DOI: 10.1613/jair.4623
|View full text |Cite
|
Sign up to set email alerts
|

Optimally Solving Dec-POMDPs as Continuous-State MDPs

Abstract: Decentralized partially observable Markov decision processes (Dec-POMDPs) provide a general model for decision-making under uncertainty in decentralized settings, but are difficult to solve optimally (NEXP-Complete). As a new way of solving these problems, we introduce the idea of transforming a Dec-POMDP into a continuous-state deterministic MDP with a piecewise-linear and convex value function. This approach makes use of the fact that planning can be accomplished in a centralized offline manner, while execut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 44 publications
1
75
0
Order By: Relevance
“…This intuition is correct [Nayyar et al, 2011, Dibangoye et al, 2013, MacDermed and Isbell, 2013. In particular, it is possible make a reduction to special type of POMDP: a non-observable MDP (a POMDP with just one 'NULL' observation).…”
Section: A Nomdp Formulationmentioning
confidence: 94%
See 1 more Smart Citation
“…This intuition is correct [Nayyar et al, 2011, Dibangoye et al, 2013, MacDermed and Isbell, 2013. In particular, it is possible make a reduction to special type of POMDP: a non-observable MDP (a POMDP with just one 'NULL' observation).…”
Section: A Nomdp Formulationmentioning
confidence: 94%
“…However, it turns out that it is possible to replace the dependence on the past joint policy by a so-called plan-time sufficient statistic: a distribution over histories and states [Oliehoek et al, 2013a, Dibangoye et al, 2013. This is useful, since many past joint policies can potentially map to the same statistic, as indicated in Figure 4.5.…”
Section: Plan-time Sufficient Statisticsmentioning
confidence: 99%
“…Recently, major strides in solving Dec-POMDPs have been made. In particular, it has been shown that there is a reduction from Dec-POMDP to a special type of centralized POMDP called a non-observable Markov decision process (NOMDP) (MacDermed and Isbell, 2013;Nayyar et al, 2013;Dibangoye et al, 2013;Oliehoek and Amato, 2014). This allows POMDP solution methods to be employed in the context of DecPOMDPs.…”
Section: Other Decision Problemsmentioning
confidence: 99%
“…Recently, a number of approaches have been developed that transform a Dec-POMDP into a continuous-state MDP and then use techniques from the POMDP literature to solve the continuous-state MDP (Dibangoye, Amato, Doniec, & Charpillet, 2013a;Dibangoye, Amato, Buffet, & Charpillet, 2013b). The state in such a continuous MDP reformulation of a Dec-POMDP, also called occupancy state, is the probability distribution over the world state and the history of observations each agent has received.…”
Section: Related Workmentioning
confidence: 99%